The effect of environmental quality on health expenditure in some selected sub Sahara Africa countries - Angelus, Efeutlancha Forji; Wujung, Vukengkeng Andrew; Mbu, Tambi Daniel (International Journal of Economics, Business, and Entrepreneurship, 2024)
This research aims to examine the effect of environmental quality on health expenditure in sub-Saharan African nations. Data from 41 some select nations in sub-Saharan Africa from 1996 to 2020 was collected from the World Development Indicators (WDI). The statistical results are calculated using the Pool Mean Group (PMG) method. The study findings revealed that greenhouse gases have a negative and insignificant relationship with health expenditure in the short run. This implies that in the short run, there is favorable environmental quality as a result of low atmospheric pollution, resulting in low environmental related diseases such as respiratory tract infection and cardiovascular disease infection, thus leading to reduced health expenditure in these selected sub-Saharan African countries. The finding further revealed that greenhouse gases have a direct and significant relationship with health expenditure in the long run. This implies that an increase in these gases, carbon dioxide, nitrogen dioxide, and ambient PM2.5, reduces the quality of the environment, which results in an increase in diseases such as respiratory tract infection and cardiovascular disease infection, thus increasing health expenditure by 0.12 units and the result was statistically significant at 1% level of significance. This increase in environmental deterioration is a result of these countries' weak trade, environmental, and institutional policies, all of which worsen already-existing problems with healthcare systems. Spending on healthcare is positively correlated with GDP per capita, with a higher GDP per capita resulting in higher healthcare spending both in the short run and the long run. The finding shows a positive relationship among population, industrialisation, and health spending. This is due to the fact that an increase in population and more industrial activities result in illnesses and environmental degradation, leading to an increase in health expenditure in the selected Sub-Saharan African countries, whereas urbanisation has a negative correlation. The co-integrated link between the variables is demonstrated by the one lag error correction term (ECT), whose coefficient of -0.4237 and statistically significant at 1% level of significance indicates a moderate level of convergence to equilibrium. The study therefore, recommends that the sub Africa countries government are recommended to strengthen environmental regulation policies, such as affordable and clean energy consumption as stipulated by sustainable development goals, restricting heavy polluting foreign industries, while encourages industries which uses advanced technology which are ecofriendly, since the most habitat activities are close to the earth, the types pesticides use for agricultural purposes should be control by restricting those are very dangerous to the environment, the level of environmental exploitation in this region should match with the ability of the environment to be able sustained future generation by limiting the amount resources of non-renewable to be exploited and encouraging enforcement of renewable resources such as afforestation by the provision of seedlings to right institutions.